Aplikasi Menemukan Rute Terdekat Lokasi Tambal Ban Menggunakan Algoritma Breadth First Search (BFS) - Ade Zulkarnain; Munjiat Setiani Asih (Journal of Informatics Management and Information Technology, 2024)
Searching for the shortest distance to a tire repair location is a problem that often arises for transportation users. Because transportation users when traveling need a solution, the route they will take is the closest route or distance. So that time efficiency can be achieved. So this research will try to develop an application system that is implemented on Android. The method used is Breadth First Search (BFS), which focuses on a wide search to nearby neighbors and looking for the shortest distance. Where in this case it can make it easier for Android users if implemented in an application system, then searching for tire patch routes will provide or display the closest distance route. Testing was carried out using an Android application using the Breadth First Search (BFS) method to determine the success conditions, so a success rate of up to 95% was obtained. This means that with these results the Breadth First Search (BFS) method implemented in an Android application is quite good